2019
DOI: 10.1371/journal.pone.0221223
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of afebrile malaria and development of risk-scores for gradation of villages: A study from a hot-spot in Odisha

Abstract: Introduction Malaria is a public health emergency in India and Odisha. The national malaria elimination programme aims to expedite early identification, treatment and follow-up of malaria cases in hot-spots through a robust health system, besides focusing on efficient vector control. This study, a result of mass screening conducted in a hot-spot in Odisha, aimed to assess prevalence, identify and estimate the risks and develop a management tool for malaria elimination. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…31 In Odisha, submicroscopic and asymptomatic infection were reported to be 30% and 79% of the total infections, respectively, in 2019. 32…”
Section: Parasite Reservoirs In Forest Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In Odisha, submicroscopic and asymptomatic infection were reported to be 30% and 79% of the total infections, respectively, in 2019. 32…”
Section: Parasite Reservoirs In Forest Populationsmentioning
confidence: 99%
“… 31 In Odisha, submicroscopic and asymptomatic infection were reported to be 30% and 79% of the total infections, respectively, in 2019. 32 Up to 8.4% of the tribal population in Bundwan block in the Purulia district, West Bengal was found to harbour Pf and all the infections were without any clinical manifestation. 33 Genotyping cognate Plasmodium falciparum in human and mosquitoes revealed that asymptomatic infections have more than double the odds of transmission to a mosquito compared with asymptomatic infections.…”
Section: Parasite Reservoirs In Forest Populationsmentioning
confidence: 99%
“…It can be a key factor in tribal populations and remote geographies in which most of the malaria exists in India and other LMICs. Detection by CHWs has been a big part of the success achieved in malaria-management by another Indian state, Odisha [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The logistic regression framework will be applied for modelling the unadjusted, adjusted, and final analyses. Once the best model is identified, a malaria risk scoring system will be developed and the allocation of points for each variable will be based on the magnitude of its regression coefficients [ 45 ]. The sum of points for each variable will be used as an approximation to rank the village from the highest to the lowest risk of malaria in the future [ 45 ].…”
Section: Methodsmentioning
confidence: 99%